2022
DOI: 10.3390/vetsci9010028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Opioid Dose on Gastrointestinal Motility in Rabbits (Oryctolagus cuniculus): Comparisons among Morphine, Butorphanol, and Tramadol

Abstract: The aim of this study was to evaluate and compare the effects of single doses of butorphanol, morphine, and tramadol on gastrointestinal motility in rabbits (Oryctolagus cuniculus) using non-invasive imaging methods, such as radiographic barium follow through and ultrasonographic contraction counts. Time-lapse radiographic and ultrasound examinations were performed before and after a single intramuscular dose of 5 mg kg−1 butorphanol, 10 mg kg−1 morphine, or 10 mg kg−1 tramadol. Pyloric and duodenal contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This molecule is commonly deemed safe when applied in rabbit anesthesia, with few adverse effects [ 13 , 20 ]. One study reported a temporary reduction in gastric motility following the administration of 10 mg kg −1 of butorphanol intramuscularly [ 37 ]. However, this dose is 20 times higher than that used in this study (0.2 mg kg −1 ); hence, the results may not be directly comparable to those of the cited study.…”
Section: Discussionmentioning
confidence: 99%
“…This molecule is commonly deemed safe when applied in rabbit anesthesia, with few adverse effects [ 13 , 20 ]. One study reported a temporary reduction in gastric motility following the administration of 10 mg kg −1 of butorphanol intramuscularly [ 37 ]. However, this dose is 20 times higher than that used in this study (0.2 mg kg −1 ); hence, the results may not be directly comparable to those of the cited study.…”
Section: Discussionmentioning
confidence: 99%
“…Morphine temporarily slows gastrointestinal transit in rabbits, but whether buprenorphine does is controversial. [33][34][35] Fluid therapy and syringe feeding are essential while the rabbit recovers until it eats and drinks adequately on its own. 36 Limitations of this study include the retrospective nature of data analysis, short follow-up length, and not performing CT scans later (3 or 6 months) to assess otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical to provide ongoing analgesia for several days, while reducing narcotic requirements in postoperative care. Morphine temporarily slows gastrointestinal transit in rabbits, but whether buprenorphine does is controversial 33–35 . Fluid therapy and syringe feeding are essential while the rabbit recovers until it eats and drinks adequately on its own 36 …”
Section: Discussionmentioning
confidence: 99%